Advances and development of prostate cancer, treatment, and strategies: A systemic review - Belkahla, Sana; Nahvi, Insha; Biswas, Supratim; Nahvi, Irum; Ben Amor, Nidhal (Frontiers in Cell and Developmental Biology, 2022)
The most common type of cancer in the present-day world affecting modern-day men after lung cancer is prostate cancer. Prostate cancer remains on the list of top three cancer types claiming the highest number of male lives. An estimated 1.4 million new cases were reported worldwide in 2020. The incidence of prostate cancer is found predominantly in the regions having a high human development index. Despite the fact that considerable success has been achieved in the treatment and management of prostate cancer, it remains a challenge for scientists and clinicians to curve the speedy advancement of the said cancer type. The most common risk factor of prostate cancer is age; men tend to become more vulnerable to prostate cancer as they grow older. Commonly men in the age group of 66 years and above are the most vulnerable population to develop prostate cancer. The gulf countries are not far behind when it came to accounting for the number of individuals falling prey to the deadly cancer type in recent times. There has been a consistent increase in the incidence of prostate cancer in the gulf countries in the past decade. The present review aims at discussing the development, diagnostics via machine learning, and implementation of treatment of prostate cancer with a special focus on nanotherapeutics, in the gulf countries.